Panos-Fermented Extract-Mediated Nanoemulsion: Preparation, Characterization, and In Vitro Anti-Inflammatory Effects on RAW 264.7 Cells - Rui Zhang; Esrat Jahan Rupa; Siwen Zheng; Jinnatun Nahar; Deok Chun Yang; Se Chan Kang; Yingping Wang (Molecules, 2021)
This study focused on developing Panos nanoemulsion (P-NE) and enhancing the anti-inflammatory efficacy for the treatment of inflammation. The effects of P-NE were evaluated in terms of Nitric oxide (NO production) in Lipopolysaccharide (LPS), induced RAW 264.7 cells, Reactive oxygen species (ROS) generation using Human Keratinocyte cells (HaCaT), and quantitative polymerase chain reaction (qPCR) analysis. Sea buckthorn oil, Tween 80, and span 80 were used and optimize the process. Panos extract (P-Ext) was prepared using the fermentation process. Further high-energy ultra-sonication was used for the preparation of P-NE. The developed nanoemulsion (NE) was characterized using different analytical methods. Field emission transmission electron microscopy (FE-TEM) analyzed the spherical shape and morphology. In addition, stability was analyzed by Dynamic light scattering (DLS) analysis, where particle size was analyzed 83 nm, and Zeta potential −28.20 ± 2 (mV). Furthermore, 90 days of stability was tested using different temperatures conditions where excellent stability was observed. P-NE are non-toxic in (HaCaT), and RAW264.7 cells up to 100 µg/mL further showed effects on ROS and NO production of the cells at 50 µg/mL. The qPCR analysis demonstrated the suppression of pro-inflammatory mediators for (Cox 2, IL-6, IL-1β, and TNF-α, NF-κB, Ikkα, and iNOS) gene expression. The prepared NE exhibited anti-inflammatory effects, demonstrating its potential as a safe and non-toxic nanomedicine.